Investigating the Effect of Soaking and Tempering Temperatures on High Vanadium Alloys for Grinding Media - Absalom D. Mabeba; Charles Siyasiya; Joseph Moema (Recent Trends in Chemical and Material Sciences Vol. 3, 2021)
Vanadium produces the hardest carbides and can influence wear properties positively [1,2]. However, due to the minerals’ price fluctuations as a result of the current economic climate, vanadium is currently expensive and seldom used in wear resistant materials despite its valuable properties. Nevertheless, it is still important to study the effects of vanadium carbides (VC) on wear properties and later compare the cost/durability ratio to the other currently used industrial alloys. Vanadium has been used as a secondary alloying element in high chromium cast iron (HCWCI) and has produced positive results through the influence of orientation and morphology of the eutectic carbide M7C3 [3,4]. VC are known to be discontinuous [5,6], which is helpful with regards to impact properties. VC alone cannot maintain high macro-hardness values and for improved results carbon (C) is needed to increase the strength of the matrix [7]. For improved wear properties, the hardness of the surface must be between 0.5 and 1.3 times the hardness of the abrasive. In this paper, the influence of the soaking and tempering temperatures on hardness and wear properties in a high vanadium alloy, 1.91C-0.82Mn-0.96Si-0.90Ni-1.35Cr-0.25Mo-6.12V, were investigated. The soaking temperatures were 1150 and 1250°C while the tempering temperatures were varied at 100°C interval from 300°C to 600°C. It was found that soaking at 1250°C increased the amount of retained austenite, but at the same time also improved the wear resistance in as-quenched condition as well as after tempering up to 500°C.